2019
DOI: 10.1096/fj.201902227r
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory network mediated by RBP‐J/NFATc1‐miR182 controls inflammatory bone resorption

Abstract: Abbreviations: Blimp1, B lymphocyte-induced maturation protein-1; BMM, bone marrow-derived macrophage; ChIP, chromatin immunoprecipitation; FAIRE, formaldehyde-assisted isolation of regulatory elements; FOXO3, Forkhead box class O 3; MNC, multinucleated cell; M-CSF, macrophage colony-stimulating factor; NFATc1, nuclear factor of activated T cells c1; PBMCs, peripheral blood monocytes; PKR, protein kinase double-stranded RNA dependent; RA, rheumatoid arthritis; RANKL, receptor activator for NF-kB ligand; RBP-J,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 65 publications
(207 reference statements)
0
12
0
Order By: Relevance
“…Throughout life, bone remodeling is precisely regulated by the balance between osteoblastic bone formation and osteoclastic bone resorption. This balance is often disturbed by diseases associated with excessive bone resorption, such as osteoporosis, rheumatoid arthritis (RA), periodontitis, and bone metastasis [ 1 , 2 , 3 ]. Osteoclasts, multinucleated cells that derive from the monocyte–macrophage lineage of hematopoietic stem cells, are responsible for bone destruction in these diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Throughout life, bone remodeling is precisely regulated by the balance between osteoblastic bone formation and osteoclastic bone resorption. This balance is often disturbed by diseases associated with excessive bone resorption, such as osteoporosis, rheumatoid arthritis (RA), periodontitis, and bone metastasis [ 1 , 2 , 3 ]. Osteoclasts, multinucleated cells that derive from the monocyte–macrophage lineage of hematopoietic stem cells, are responsible for bone destruction in these diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Through genome-wide miRNA expression profiling, our group identified miR-182 as a TNF-induced miRNA that is directly targeted and suppressed by RBP-J in bone marrow macrophages and osteoclast precursors ( 46 , 47 ). RBP-J inhibits the expression and function of NFATc1 ( 25 ), which in turn acts as an upstream regulator activating miR-182, pointing to a novel regulatory network ( 48 ). Both in vitro and in vivo evidence supports the role of miR-182 as a positive regulator of TNF-mediated osteoclastogenesis.…”
Section: Rbp-j Targets and The Regulatory Network Mediated By Rbp-j/nmentioning
confidence: 99%
“…Potential long-term side effects on physiological bone remodeling by targeting these mechanisms should especially be given attention. Recent studies identified novel TNF-induced intrinsic inhibitory mechanisms of osteoclastogenesis, which are unique from RANKL-mediated mechanisms ( 25 , 32 , 48 ). Exploring these mechanisms would shed insight into developing selective therapeutic approaches to prevent TNF-mediated bone resorption associated with inflammatory diseases, without undesirably impacting physiological bone remodeling.…”
Section: Clinical Relevance Of Tnf-induced Inhibitory Mechanisms In Imentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that FOXO3a levels were significantly decreased in RA patients compared with healthy individuals. 21,[23][24][25][26] However, Kuo and Lin 20 and Grabiec et al 22 showed the opposite results and found no significant difference in FOXO3a levels between RA patients and healthy controls. In addition, Min et al 18,27 and Kim et al 28 observed that FOXO3a levels in IBD patients were different from controls, whereas other studies 20,29 reported that there were no significant differences between SLE patients and healthy individuals.…”
mentioning
confidence: 98%